Peran Kepemimpinan, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan : Studi Kasus di Indomedia Promotion - Nur Aini Hidayati; Abdul Chamid (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
In a company will be found aspects of leadership, motivation, and work discipline. This study aims to determine the role of leadership, motivation, and work discipline on employee performance in a company. Indomedia Promotion is an advertising company that has implemented these aspects. This research uses the descriptive qualitative method which is a research method by observing and describing the situation in the field specifically, transparently, and deeply. The results of this study are based on the observations of observers who have conducted an internship program at the company. The results of the study were also obtained based on the results of interviews with several employees who occupy positions in a division in the company. The conclusion from this research is that leadership has a very important role in employee performance by applying motivation and work discipline. The better the employee's performance, the easier it is for the company to achieve its goals